Interleukin 12 induction of interferon gamma-dependent protection against malaria. - Sedegah, M (1994)
Intraperitoneal injection of recombinant Interleukin 12 (rIL-12) at 30 ng/day for 5 days beginning 1 to 2 days before sporozoite challenge or administration of a single dose of 150 ng of rIL-122 days before challenge protected 100% of BALB/c mice against challenge with 10(2) Plasmodium yoelii sporozoites. rIL-12-induced protection was eliminated in all mice by administration of a monoclonal antibody against interferon gamma and in 50% of mice by administration of NG-monomethyl-L-arginine, a competitive inhibitor of nitric oxide synthase. rIL-12 protected BALB/c mice treated with cytotoxic anti-CD4 and anti-CD8 monoclonal antibodies, as well as T-cell- and B-cell-deficient severe combined immunodeficiency mice. These data suggest that rIL-12 stimulates non-B, non-T cells to produce interferon gamma that kills intrahepatic parasites by stimulating nitric oxide production. If rIL-12 proves to be well tolerated by humans, our findings support consideration of rIL-12 as an immunoprophylactic against malaria.